Challenges and Instructional Strategies of Elementary School Teachers in Delivering IPAS Learning within the Framework of the Merdeka Curriculum - Nadia Ayu Pramudita; Sulthan Ali Hakim; Surayanah Surayanah; Marsanda Avilia Putri (Al Hikmah: Journal of Education, 2026)
The implementation of IPAS (Integrated Natural and Social Sciences) within the Merdeka Curriculum has transformed learning practices in Indonesian elementary schools by requiring teachers to integrate scientific and social concepts through contextual and student-centered learning activities. However, the transition to this curriculum presents various challenges for teachers, particularly related to limited learning resources, instructional facilities, and the diverse learning characteristics of students. This study aimed to identify the challenges encountered by elementary school teachers and to describe the instructional approaches applied in delivering IPAS learning under the Merdeka Curriculum. The research employed a descriptive qualitative design. Data were collected through classroom observations, in-depth interviews with fourth-grade teachers at UPT SP SDN Bendo 1, Blitar City, and document analysis of lesson plans, teaching materials, and assessment instruments. The document analysis was conducted using content analysis to examine alignment with IPAS learning objectives and the Merdeka Curriculum guidelines. The findings reveal that teachers faced several obstacles, including limited learning media, inconsistencies in learning resources, and variations in students’ learning abilities that influenced classroom implementation. To overcome these challenges, teachers utilized the surrounding environment as a learning resource, implemented experiential learning approaches, strengthened collaboration with parents, and participated in professional discussions with fellow teachers. The study highlights that sustained institutional support, adequate learning facilities, targeted teacher training, and continuous professional development activities—such as workshops, teacher working group forums, and collaborative lesson planning—are key factors in enhancing the quality and effectiveness of IPAS learning in elementary schools implementing the Merdeka Curriculum.